Conservation of the breeding population of Lesser Adjutant Stork - Subba, Bharat Raj; Limbu, Kul Prasad; Surana, Ranjana (Our Nature, 2009)
In and around Koshi Tappu Wildlife Reserve, Eastern Nepal Grantee: Bharat Raj Subba The Lesser Adjutant Stork (Leptoptilos javanicus), one of the eight species of storks found in Nepal, is globally threatened. The overall objective of the project is to ensure that the populations of Lesser Adjutant Stork found in the human-dominated landscape of eastern Nepal are conserved and the threats to their survival reduced. The study will determine the breeding success of the species in and around the Koshi Tappu Wildlife Reserve, document current threats and develop an awareness campaign for its survival. The project is funded by CEPF and WWF.